Risk probability assessment of winter wheat net primary productivity loss and its driving factors in North China Plain - Wu, Jiujiang; Gu, Yuhui; Wang, Nan; Shen, Hongzheng; Ma, Xiaoyi (Field crops research, 2023)
In agroecosystems, net primary productivity (NPP) plays a vital role in the global terrestrial carbon cycle and is closely associated with crop yields. Although wheat is a major grain crop in China, the potential risk of NPP loss in winter wheat cultivation remains a topic of debate. In this study, we evaluated the risk of NPP loss in winter wheat and identified its drivers using Bayesian theory. We focused on the North China Plain (NCP), the largest winter wheat cultivation region in China. We examined various factors, including climate variables (temperature and precipitation), extreme weather events (agricultural drought, heat stress, and late frost stress), and phenology, that may affect the likelihood of winter wheat NPP loss. We divided the study area into three regions according to the amount of precipitation during the cultivation period of winter wheat: Region 1 (precipitation > 250 mm), Region 2 (150 mm < precipitation < 250 mm), and Region 3 (precipitation < 150 mm). The NPP relative losses of winter wheat was observed to decrease in the study area over the study period. Compared with Region 2, Region 3 experienced lower relative loss but at a greater uncertainty. However, Region 3 exhibited greater adaptability with regard to high loss risks. In Regions 1, 2, and 3, the spatial distribution of the risk index (RI) was primarily influenced by agricultural drought, precipitation, and heading date, respectively, with agricultural drought being the main driver of interannual variations in the RI. In the presence of extreme weather events, the length of the phenological process indirectly influenced the NPP loss of winter wheat. Overall, this study highlights the characteristics of winter wheat NPP loss and its underlying risk factors in different regions of the NCP. Our findings suggest that effectively controlling the phenological processes of winter wheat can mitigate the negative effects of extreme weather events. These findings contribute to our understanding of the regional carbon cycle and to efforts at optimizing field management strategies. •Loss risk of winter wheat NPP was assessed based on Bayesian,•The relative loss of NPP in winter wheat ranged from 4.2 % to 7.1 %,•Agricultural drought as an interannual driver of risk index,•Heading date had the highest average contribution to the risk index with 20.89 %,